Prospective analytical study on acute pulmonary edema in obstetric intensive care unit - Nagaraj, Prasanna; Meganathan, Harilakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Acute pulmonary oedema is an uncommon,but life threatening event in pregnancy. It causes significant morbidity and mortality due to pathophysiology of pre‐eclampsia and physiological changes of pregnancy which may aggravate certain pre-existing heart disease. Methods: This study was conducted to describe the clinical and epidemiological profile of antenatal women with acute pulmonary edema in obstetric ICU from January 2017 to December 2018 (2 years) in Mahathma Gandhi Memorial Government Hospital, Trichy, Tamil Nadu, India. Results: Acute pulmonary edema (n=31) accounts for 2.7% of ICU/HDU admissions in the study period. Most common etiology observed was severe preeclampsia (12 cases) followed by cardiogenic pulmonary edema (11 cases). Fluid overload, sepsis accounted for 7 cases and one mother with preexisting RHD had severe pre-eclampsia with acute pulmonary edema. Conclusions: Hypertensive disorders of pregnancy and heart disease contributes to major proportion of acute pulmonary edema in this study and it is imperative to recognize signs of critical illness. Skilled multidisciplinary teamwork plays an important role in optimizing maternal and fetal health.